Perkembangan Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat Tahun 2012-2020 - Arianda Arianda; Kaksim Kaksim; Juliandri Kurniawan Junaidi (Galanggang Sejarah, 2021)
This study aims to examine the development of Nagari in Lembah Melintang Sub-district in 2012-2020, starting with the transition of the leadership of Wali Nagari from M. Thamrin (Elected Wali Nagari for the period 2005-2011) to Burhanuddin. Z (Wali Nagari elected for the period 2012-2018) until 2020 or under the leadership of Wali Nagari Padri lubis (temporary Wali Nagari to date). This research was conducted using historical research methods by going through several stages, namely: first heuristics is the collection of various sources in the form of archives, documents, interviews, literature sources related to research studies. The second is source criticism, namely testing the sources collected by researchers through internal and external criticism. The third interpretation is interpreting these sources and connecting them so that there is a link between the facts of the study and they are neatly arranged both in terms of space and time. Fourth Historiography is to present the results of the research in the form of a written work. The results of this study indicate the desire of the Nagari Government to create or prosper its people. This is evidenced by the construction of facilities or facilities that support quality human resources as well as development to create business opportunities for local communities in order to obtain a better economic life.